Peran Teknologi Informasi dalam Peningkatan Tata Kelola Sumber Daya Manusia: Studi Kasus Sistem Informasi Kepegawaian SIMASTER - Abim Sastrawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2026)
This study aims to analyze the contribution of the Integrated Civil Servant Management Information System (SIMASTER) in improving human resource governance within government institutions. The research is grounded in the growing need for digital transformation to enhance the efficiency, effectiveness, and transparency of personnel administration. Using a qualitative approach through literature review and document analysis, this study examines implementation reports and supporting data related to SIMASTER. The findings indicate that the system significantly accelerates administrative processes, reduces manual resource usage, and lowers operational costs. In terms of effectiveness, SIMASTER improves data accuracy, speeds up performance information processing, and enhances employee satisfaction with digital personnel services. The system also strengthens transparency through open data access and digital audit mechanisms that minimize the risk of data manipulation. The study concludes that SIMASTER plays a strategic role in advancing bureaucratic reform and modernizing human resource management. Recommendations include strengthening staff competencies, improving system security, and fostering a digital work culture.